Experimental comparison of various techniques for spot size measurement of high-energy X-ray sources - 王毅 李勤 陈楠 程晋明 李成刚 李洪 龙全红 石金水 邓建军 (中国物理C：英文版, 2016)
In flash-radiography experiments, the quality of the acquired image strongly depends on the focal size of the X-ray source spot. A variety of techniques based on imaging of the pinhole, the slit and the rollbar are adopted to measure the focal spot size of the Dragon-I linear induction accelerator. The image of the pinhole provides a two-dimensional distribution of the X-ray spot, while those of the slit and the rollbar give a line-spread distribution and an edge-spread distribution, respectively. The spot size characterized by the full-width at half-maximum and that characterized by the LANL definition are calculated for comparison.